2007
DOI: 10.1177/153303460700600303
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Stereotactic Radiotherapy Boost and Weekly Paclitaxel in Malignant Gliomas Clinical and Pharmacokinetics Results

Abstract: Management of Malignant Gliomas continues to be a challenge. We prospectively studied the role of adding weekly Paclitaxel to Fractionated Stereotactic Radiation Therapy (FSRT) in the treatment of Malignant Gliomas. Twenty-three Glioblastoma Multiforme and two Anaplastic Astrocytoma were studied. Patients received 46 Gy at 2 Gy/fraction followed by a boost utilizing FSRT at a fraction of 2.5 Gy for 8 fractions. Paclitaxel is delivered concomitantly at 150 mg/m(2) weekly for six cycles. Eighteen patients had ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It has exhibited potent cytotoxicity against malignant gliomas by intratumoral convection-enhanced delivery in Phase I/II clinical studies and combination therapy with topotecan and filgrastim or fractionated stereotactic radiotherapy in clinical trials. [24][25][26] Recent in vitro studies have shown that after MSC uptake, the active form of Ptx can be released from MSC Ptx via the Pgp system or via membrane microvesicles, giving MSCs their strong antitumor activity. 14,27 However, cell dysfunction after Ptx priming, mechanical filtration of circulating MSCs, and the bloodbrain barrier make convenient systematic injection methods challenging, including injections into the tail vein, femoral vein, and carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…It has exhibited potent cytotoxicity against malignant gliomas by intratumoral convection-enhanced delivery in Phase I/II clinical studies and combination therapy with topotecan and filgrastim or fractionated stereotactic radiotherapy in clinical trials. [24][25][26] Recent in vitro studies have shown that after MSC uptake, the active form of Ptx can be released from MSC Ptx via the Pgp system or via membrane microvesicles, giving MSCs their strong antitumor activity. 14,27 However, cell dysfunction after Ptx priming, mechanical filtration of circulating MSCs, and the bloodbrain barrier make convenient systematic injection methods challenging, including injections into the tail vein, femoral vein, and carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the concomitant delivery of paclitaxel with radiation in patients with GBM. Ashamalla et al [62] observed that the concomitant administration of paclitaxel with radiotherapy to GBM patients was well tolerated and resulted in an overall survival of 14 months. Julka et al [63] also reported on a similar treatment approach in GBM patients and showed that the overall survival rate at 1 year was 70% with a combined paclitaxel/radiotherapy treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects were severe acute hypersensitivity, anemia, neutropenia, thrombocytopenia, leucopenia, arthralgia, peripheral neuropathy, alopecia, mucositis, nausea/vomiting and diarrhea. PTX can cause shortness of breath, hypotension, angioedema, urticaria, flushing rash et al Considering its serious side reaction it is very important to reduce PTX dosage but maintain the same treatment effect (11). So we consider that PTX should combine with other treatments such as gene therapy.…”
Section: Discussionmentioning
confidence: 98%